New Look at the Economic Well-Being of the Elderly in the United States, 1989-2001 - Wolff, Edward; Zacharias, Ajit (Journal of Income Distribution®, 2009)
We examine the economic well-being of the elderly, using the Levy Institute Measure of EconomicWell-Being (LIMEW). The LIMEW is a comprehensive measure that incorporates broader definitions of income, from wealth, government expenditures, and taxes, than standard income and also includes the value of household production. We find that the elderly are much better off relative to the non-elderly according to the LIMEW than according to the money income or the Census Bureau’s “Extended Income” (EI) concept. The main reason is the much higher income from wealth and net government expenditures for the elderly than for the non-elderly. Both mean and median measures of the LIMEW also grew much faster for the elderly than for the non-elderly over the period 1989-2001. In contrast, growth rates of money income were actually greater for the non-elderly than for the elderly over this period. We also find that the degree of inequality in the LIMEW is substantially higher among the elderly than among the non-elderly. In contrast, inequality in EI is virtually identical between the two groups. Inequality in the LIMEW grew for both the elderly and the non-elderly, while the inequality in EI (as well as in standard money income) grew only for the latter group.